Signs of Royalty: an Analysis of Symbols on Traditional Kings' Graves in Raja Prailiu Village (Lembaga Pengembangan Kinerja Dosen, 2023)
“Signs of Royalty: An Analysis of Symbols on Traditional Kings' Graves in Raja Prailiu Village” is a semiotic study that aims to find out the symbols of the stone tomb carved on the traditional kings’ graves and their meanings by using Pierce’s theory. All the data gained are analyzed using the descriptive qualitative method. The instruments used in this research are observation and interview. The result of the research showed that there are twelve (12) symbols found on the kings’ traditional graves,they are Manu Wulu (roaster), Njara (horse), Tau (human), Ahu (dog), Ana wuya rara (crocodile), Ruha (deer), Lamba (jewelry), Na Ana Lodo Na Ana Wullang (the sun and moon), Ana Kara Wula (turtle), Maduku Pati (coffin bearer), Maduke (animal slaughter), and Papaha Maramba (queen).